The Interplay Between Fiscal Institutions and the Great Recession: Evidence From U.S. School Districts - Christian Buerger; Michelle L. Lofton (SAGE Publishing, 2023)
Recessions may disproportionally affect school districts, especially with established fiscal institutions and policies including balanced budget requirements, tax and expenditure limitations, and school finance reforms. Analyzing the Great Recession and school districts in the United States between 2003 and 2016, we estimated difference-in-differences models leveraging variation in state recession severity to evaluate revenue and expenditure impacts as well as to measure differential recession effects for districts exposed to and not exposed to fiscal institutions and policies. Although revenues and expenditures increased relative to pre-recession levels in all districts, increases were much larger in school districts with less severe than more severe recessions. Balanced budget requirements exacerbated recession effects for low-income districts, and local tax and expenditure limitations intensified recession effects for high-income districts. School finance reforms worsened recession effects for all districts. Our findings can aid districts in understanding potential recessionary impacts, given their prior established fiscal policies and institutions.